NEED ANALYSIS IN LEARNING ENGLISH FOR NON ENGLISH PROGRAM AT TARBIYAH AND TEACHER TRAINNING FACULTY - Yuwin Rustam Saleh (Al-Lisan: Jurnal Bahasa, 2018)
This research aims to obtain information about the needs of learners in Englih learning especially non English department students surroundings of Tarbiyah and teacher training Faculty of IAIN Sultan Amai Gorontalo, the results of the analysis of data obtained via the questionaire form as the main instrument. Based on the data analysis, it was obtained information that the English material should be submitted by using the strategies varied, English has four skills with more emphasized on a competency-based vocabulary , this is because learners expected through vocabulary they can understand a textbook material on other subjects which is very useful for them in job field.